Gastrointestinal Stromal Tumor Induced Hypercalcemia - Barbaryan, Aram (Case Rep Oncol Med, 2017)
Hypercalcemia in patients with cancer is a common laboratory finding affecting up to 44% of that patient population. 1,25-Dihydroxyvitamin D(3) mediated hypercalcemia is one of the rare mechanisms of this endocrine emergency in cancer patients. It is even rarer for solid organ neoplasms to present with hypercalcemia mediated through the production of 1,25-dihydroxyvitamin D(3). We report a case of a 77-year-old female who presented to the hospital with hypercalcemia and later was found to have metastatic gastrointestinal stromal tumor. There have been only 5 cases of gastrointestinal stromal tumor described in literature resulting in hypercalcemia. In our case, the mechanism of hypercalcemia was thought to be related to overproduction of 1,25-dihydroxyvitamin by tumor cells. The patient had a favorable response to imatinib with normalization of serum calcium level. Unfortunately, she developed fluid retention due to imatinib which was discontinued resulting in relapse of hypercalcemia that was resistant to all other treatment options.